Who is in the game? Net-mapping as a tool to find stakeholders in a food system - Habermann, Birgit (CGIAR System Organization, 2022)
Net-mapping is a mapping tool based on group interviewing. It helps to visualize certain situations where many different actors can influence outcomes. A net-map helps us to understand the actors are involved in the network, the nature of their linkages are, the extent of their influence on what and whom, and their goals.